2019
DOI: 10.1002/14651858.cd009841.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Potentiators (specific therapies for class III and IV mutations) for cystic fibrosis

Abstract: Potentiators (specific therapies for class III and IV mutations) for cystic fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 93 publications
0
11
0
Order By: Relevance
“…Ivacaftor (Kalydeco ® ) was the first CFTR modulator available and is a CFTR potentiator that augments anion transport by increasing CFTR channel‐open probability 6 . It was shown to improve FEV1 lung function, reduce pulmonary exacerbations, the need of hospitalization and IV (intravenous) antibiotics in patients with gating mutation G551D 7 . Post hoc analysis further revealed the potential benefit ivacaftor has in improving weight gain in both age‐adjusted paediatric and adult patients 8 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Ivacaftor (Kalydeco ® ) was the first CFTR modulator available and is a CFTR potentiator that augments anion transport by increasing CFTR channel‐open probability 6 . It was shown to improve FEV1 lung function, reduce pulmonary exacerbations, the need of hospitalization and IV (intravenous) antibiotics in patients with gating mutation G551D 7 . Post hoc analysis further revealed the potential benefit ivacaftor has in improving weight gain in both age‐adjusted paediatric and adult patients 8 .…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…Recent clinical studies show that CFTR potentiators (e.g., Ivacaftor) successfully correct these defects in patients with these mutations [75,76,77,78]. Class IV mutations lead to disruptions in the chloride conducting capacity of the CFTR protein because of missense mutations and protein misfolding (e.g., R117H) [79,80]. Class V mutations include missense mutations that lead to a decrease in CFTR protein synthesis, resulting in a low abundance on the cell surface (e.g., A455E) [81].…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…This question is best addressed with Ivacaftor (Kalydeco), which has now been administered to individuals with CFTR gating mutations for more than seven years [41]. At this pre-conference meeting it was shown that robust Ivacaftor-induced improvements in ion transport, airway surface liquid height and ciliary beating in vitro by cultured human bronchial epithelial cells correlated well with clinical parameters, including reduced sweat chloride concentration, improved lung function (measured by forced expiratory volume in one second; FEV 1 ), increased mucus clearance and reduced lung inflammation and exacerbations [42] (IS-G, PCM). Clearly, targeting the cause of CF relieves clinical manifestations.…”
Section: The Clinical Benefit Of Allosteric Modulation Of Cftr Functionmentioning
confidence: 99%